Analysis of Creative Economy Development Model in Supporting Economic Growth - Aminah Lubis; Mutiara Shifa; Rezario Febrianta Chandra; Munazar Rafsanjani Muarif; Donny Dharmawan (LPPPIPublishing, 2026)
The creative economy is a vital new growth engine in the digital age, transforming ideas into economic and social wealth. The goal of the creative economy is to drive economic growth, create new jobs, improve social welfare, and enhance national competitiveness by utilizing ideas, creativity, and innovation as key resources, while simultaneously preserving culture and strengthening national branding. The purpose of this study was to analyze creative economy development model in supporting economic growth. This research is answered using a research method approach with a theoretical model explanation. This theoretical model is supported by sources copied from published media such as books, journals, and related sources. The research results show that the strategy for implementing a creative economy development model in supporting economic growth involves synergizing human resources, innovation, and nation branding.